THE ART OF WRITING AN ESSAY - Matqurbonova Ro’zaxon Zokirjon qizi (TADQIQOTLAR, 2025)
Abstract:  Essay  writing  is  a  crucial  skill  that  combines  creativity,  critical thinking, and structured expression. Mastering this art involves understanding the key components such as clarity, coherence, and argumentation. This article explores the essential  elements  of  essay  writing,  emphasizing  the  importance  of  planning, organization, and revision in producing a compelling piece. By focusing on effective techniques,  writers  can  develop  their  skills  and  create  essays  that  effectively communicate their ideas.